2021
DOI: 10.1021/acsfoodscitech.1c00149
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Proximate Compositions, Nutritional Minerals, Pasting Properties, and Aroma Differences of Flours from Selected Yellow Pea Cultivars Grown across the Northern Great Plains

Abstract: This research aimed to understand functionality and aromatic compound differences of yellow pea (YP) flours as affected by seven YP cultivars. All of the grains were ultracentrifugally milled to superfine flours with a particle size range of 7–58 μm. The ash, crude protein, lipid, and total starch contents of these flours were in the ranges of 2.21–3.10%, 22.50–28.69%, 0.99–3.43%, and 43.62–49.60%, respectively. Most of the flours were good natural sources of Mg, P, K, Cu, Fe, Mn, and Se. The pasting propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Native yellow pea flour was generously provided by Prof. Jiajia Rao's lab at North Dakota State University. It has been reported that the ash, crude protein, lipid, and starch contents of this pea flour is in the range 2.2-3.1%, 22.5-28.7%, 1.0-3.4%, and 43.6-49.6%, respectively [23]. The proteins were extracted from this flour using a previously described method [18].…”
Section: Methodsmentioning
confidence: 99%
“…Native yellow pea flour was generously provided by Prof. Jiajia Rao's lab at North Dakota State University. It has been reported that the ash, crude protein, lipid, and starch contents of this pea flour is in the range 2.2-3.1%, 22.5-28.7%, 1.0-3.4%, and 43.6-49.6%, respectively [23]. The proteins were extracted from this flour using a previously described method [18].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies suggested that pea was rich in diverse metabolic components. Headspace solid-phase microextraction gas chromatography-mass spectrometry combined with untargeted metabolomic approaches differentiated the aromatic profiles of seven yellow pea flours [3]. In order to study the in vivo antioxidant activities of green pea hull (GPH), a total of 31 phenolics, comprising four phenolic acids, 24 flavonoids, and three other phenolics, were tentatively identified using ultra-high-pressure liquid chromatography with Orbitrap mass spectrometry [4].…”
Section: Introductionmentioning
confidence: 99%